2022
DOI: 10.1016/j.jsxm.2022.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Are Radial Pressure Waves Effective for the Treatment of Moderate or Mild to Moderate Erectile Dysfunction? A Randomized Sham Therapy Controlled Clinical Trial

Abstract: Introduction Radial wave therapy is commercialized as an option for the management of erectile dysfunction. However, the mechanism of action of the radial waves differs substantially from shock waves, so the evidence gathered for shock wave therapy cannot be extrapolated, and there are very few clinical trials with the radial wave. Aim To assess the efficacy and safety of radial wave therapy compared with sham therapy for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
1
1
Order By: Relevance
“…In this trial, with 10 patients per arm, rWT significantly improved IIEF-5 scores at 3 months after treatment compared to sham. Sandoval-Salinas et al, reported a randomized controlled trial of men with mild or moderate ED treated with rWT or sham therapy (40 men per arm) and found no differences in IIEF-5 score and EHS (24). While our primary endpoint also had no difference in IIEF-5 scores between the arms, we did find a significant difference in EHS.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…In this trial, with 10 patients per arm, rWT significantly improved IIEF-5 scores at 3 months after treatment compared to sham. Sandoval-Salinas et al, reported a randomized controlled trial of men with mild or moderate ED treated with rWT or sham therapy (40 men per arm) and found no differences in IIEF-5 score and EHS (24). While our primary endpoint also had no difference in IIEF-5 scores between the arms, we did find a significant difference in EHS.…”
Section: Discussioncontrasting
confidence: 44%
“…The data supporting the use of rWT in ED is limited (22); at our institution the results of rWT treatment for men with vasculogenic ED was equivalent to fSWT (23). However, Sandoval-Salinas et al found no difference between rWT and sham (24). Despite the limited data, rWT is often marketed directly to consumers as evidence-based treatment for ED (25).…”
Section: Introductionmentioning
confidence: 68%